ANALISIS PENAMAAN TEMPAT USAHA FOTOKOPI DI LINGKUNGAN SEKITAR UNIVERSITAS SAMUDRA - Siti Zahara; Yuli Sartika Ginting; Naura Latifa; Floracita Sagala; Prima Nucifera (Universitas Nias Raya, 2026)
This study aims to describe the motivations behind the naming of photocopy businesses located in the area surrounding Samudra University. The study was conducted to gain a deeper understanding of the linguistic and sociocultural factors that influence business naming practices in the local community. A qualitative descriptive approach was employed to examine the reasons for the naming of these businesses and to provide a detailed explanation of the meanings associated with each business name. Data were collected through interviews with business owners, note-taking techniques, and documentation of relevant information obtained during the research process. The findings reveal that different motivations underlie the naming of photocopy businesses in the area. The name Ram Fotocopy was motivated by several factors, namely the founder or creator of the business, the use of abbreviation, and resemblance to an existing name or expression. Meanwhile, the name Prima Fotocopy was motivated by the attribution of a distinctive characteristic, reflecting positive qualities that the owner wished to associate with the business. In contrast, Krue Seumangat Dua was named based on its place of origin, indicating a connection between the business and a particular geographical location. These findings suggest that the naming of photocopy businesses around Samudra University is influenced by a variety of linguistic, cultural, and social factors that reflect the identities, values, and backgrounds of the business owners.